Spatiotemporal variability of drought in the northern part of northeast China. Issue 10 (23rd April 2018) - Zhang, Xuanwen; Liu, Xiaohong; Wang, Wenzhi; Zhang, Tingjun; Zeng, Xiaomin; Xu, Guobao; Wu, Guoju; Kang, Huhu
Abstract: The thermal and moisture balance of permafrost regions has been altered by global warming, profoundly influencing vegetation dynamics and forest carbon cycling. To understand the spatial and temporal characteristics and driving forces responsible for changes in moisture conditions in the permafrost region of the Greater and Lesser Hinggan Mountains, northeastern China, we assessed long‐term trends for temperature, precipitation, and the standardized precipitation‐evapotranspiration index. From 1951 to 2014, annual mean temperature had a significant increase trend and the annual precipitation was not with significant trend. Since 1951, the annual standardized precipitation‐evapotranspiration index has decreased significantly at the boundary between regions with seasonal soil freezing and permafrost, suggesting that conspicuous permafrost degradation and moisture loss has occurred. The study area can be divided into 4 parts with a different balance between thermal and moisture conditions: the northern Songnen Plains, the Hulun Buir Sand Land, the middle reaches of the Heilongjiang River, and the Mohe region. However, only the middle reaches of the Heilongjiang River showed an obvious long‐term drying trend. The 4 areas showed quasi‐periodic oscillation and sea surface temperature during the winter half‐year affected drought intensity in the northern of Songnen Plains. When El Niño strengthened, moisture conditions increased in the northern of Songnen Plains, whereas stronger La Niña events decreased water availability. The result of this study will be beneficial for regional water resource management and prepare for potential drought hazards in the northeastern China.